2017
DOI: 10.1038/s41699-017-0024-4
|View full text |Cite
|
Sign up to set email alerts
|

An in situ and ex situ TEM study into the oxidation of titanium (IV) sulphide

Abstract: Titanium (IV) sulphide (TiS 2 ) is a layered transition metal dichalcogenide, which we exfoliate using liquid phase exfoliation. TiS 2 is a candidate for being part of a range of future technologies. These applications are varied, and include supercapacitor and battery energy storage devices, catalytic substrates and the splitting of water. The driving force behind our interest was as a material for energy storage devices. Here we investigate a potential failure mechanism for such devices, namely oxidation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…MCs can exhibit multiple polymorphs ( e. g ., the 2H, 1T, and 3R phases of MoS 2 ) [76] and stoichiometric variants ( e. g ., PtSe 2 and PtSe), [77] and transformations between these phases can occur under various conditions. Furthermore, MCs can contain defects (vacancies, dislocations, and grain boundaries), [78] and they may readily react with environmental species to form oxides [79] or oxychalcogenides [30] . In situ experimental techniques are critical for measuring changes in material structure and chemistry under exposure to different chemical or thermal conditions.…”
Section: Structural and Chemical Transformations In Layered Chalcogenmentioning
confidence: 99%
“…MCs can exhibit multiple polymorphs ( e. g ., the 2H, 1T, and 3R phases of MoS 2 ) [76] and stoichiometric variants ( e. g ., PtSe 2 and PtSe), [77] and transformations between these phases can occur under various conditions. Furthermore, MCs can contain defects (vacancies, dislocations, and grain boundaries), [78] and they may readily react with environmental species to form oxides [79] or oxychalcogenides [30] . In situ experimental techniques are critical for measuring changes in material structure and chemistry under exposure to different chemical or thermal conditions.…”
Section: Structural and Chemical Transformations In Layered Chalcogenmentioning
confidence: 99%
“…Oxygen contamination might come from insufficient drying process due to the strong hygroscopic properties of CaCl2. [22,39] The residual oxygen may be reduced in a longer electrolysis time because of the slow diffusion of oxygen in solid. Besides, Noguchi et al [22] also investigated the effect of dehydration on the residual oxygen contents of the samples, and they showed that Ti powder with 0.42 mass% O could be obtained from CaTiO3 at Q/Q0 = 600%.…”
Section: B Electrochemical Reduction Of the Titanium Sulfides By Camentioning
confidence: 99%
“…22 However, bulk TiS 2 is also well-known to be unstable in ambient conditions, not to mention its monolayer form, which would be quickly oxidized presumably due to the oxygen and water vapor in the air. 7,23 In order to fully develop the potential use of TiS 2 for any single-layer device, transferring the intact quality of 2D crystal and direct observing its pristine lattice structure without oxidation are prerequisite.…”
Section: -mentioning
confidence: 99%